Selection of S1 lines of purple maize (Zea mays L.) var. popcorn based on segregation analysis of value traits - Huanuqueño, Hugo (2021)
Genetic improvement to obtain purple popcorn hybrids from native corn is in its initial phase. The development of hybrids not only gives you the possibility to complement valuable traits, but also, it is a means to take advantage of superior combinations that express heterosis. However, the first step is to evaluate a large number of lines. Therefore, this research seeks two objectives: (1) to analyze the mode of segregation of the value characters: expansion volume (VE), grain expansion (EG), black pericarp (PN) and grain yield (RG) and (2) select outstanding S1 lines for VE and PN. For this, 256 segregating lines were evaluated in three experiments, one in Huánuco at 1986 msnm and two in La Molina at 241 msnm. The tests were installed under the Simple Latice 16x16 design with two repetitions. It was determined that the continuous distribution mode with mostly additive alleles is the one that predominates in the expression of the VE, EG, PN and RG traits, however, in the VE, EG and RG characteristics, a certain dominance of genes was observed with low values ​​and in PN, the presence of three modes was noted, which would possibly indicate the presence of genes with greater effects. Considering the distribution mode and the phenotypic values of the 256 S1 lines for the VE and PN value characters, a selection index was established that allowed the identification of 80 outstanding lines that represent a selection pressure of 31.25%.